2015
DOI: 10.1093/geront/gnv100
|View full text |Cite|
|
Sign up to set email alerts
|

Delirium Screening: A Systematic Review of Delirium Screening Tools in Hospitalized Patients

Abstract: The Confusion Assessment Method was the most widely used instrument to identify delirium, however, specific training is required to ensure optimum performance. The Delirium Rating Scale and its revised version performed best in the psychogeriatric population but requires an operator with psychiatric training. The Nurses' Delirium Screening Checklist appears best suited to the surgical and recovery room setting. The Single Question in Delirium shows promise in oncology patients. The Memorial Delirium Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
183
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(202 citation statements)
references
References 67 publications
2
183
1
5
Order By: Relevance
“…An ideal screening tool for delirium should be brief, require little or no training, and be appropriate to the clinical setting it is used in. It should prioritise high sensitivity over specificity, reliably detecting those with delirium and also have acceptable specificity, accurately identifying those without delirium as screen negative [6].…”
Section: Introductionmentioning
confidence: 99%
“…An ideal screening tool for delirium should be brief, require little or no training, and be appropriate to the clinical setting it is used in. It should prioritise high sensitivity over specificity, reliably detecting those with delirium and also have acceptable specificity, accurately identifying those without delirium as screen negative [6].…”
Section: Introductionmentioning
confidence: 99%
“…Even CAM is already assessed in so many times, the sensitivity and specificity remain in a good shape (De & Wand, 2015). Currently, one study reported that the sensitivity of CAM ranges from 40-100%, while the specificity ranges from 63-100%.…”
Section: Discussion Early Delirium Assessment In Hospitalized Older Pmentioning
confidence: 99%
“…Nurse Media Journal of Nursing, 6 (1), 2016, When it comes to assessing delirium in older people, CAM only takes several minutes, when compared to other questionnaire (De & Wand, 2015). CAM is also available in some modified forms, which can be set up for different needs/settings.…”
Section: Discussion Early Delirium Assessment In Hospitalized Older Pmentioning
confidence: 99%
“…6,8 The adaptationof instruments for the evaluation of subjective constructs,for different languages and cultures, has also been the subject of a large number of investigations, including discussions on the appropriate methodological process to ensure that the instrument preserves its properties of validity and reliability after adaptation. 1 In the last decade, this type of research has produced a considerable number of nursing researches, [9][10][11][12][13] reflecting the concern of these professionals to identify the most appropriate measurement instrument for a given situation or condition, considering the one that addresses the monitoring of patients in clinical practice and that contemplates the perception of the individuals themselves in the evaluation of their state of health. 14 From the analysis of the increase in measurement instruments available in the scientific literature, the authors identified two important aspects to be overcome: the need to identify the available questionnaires for a specific use in the various subjects, so that they may be known to interested professionals and the need to know the measures that would be considered more appropriate (valid and reliable) among the various available instruments.…”
Section: Introductionmentioning
confidence: 99%